시간에 따른 회전 및 하중을 고려한 강체 동역학 해석에 기반한 베어링 성능 평가 - 이승표(Seungpyo Lee) (Tribology and Lubricants, 2023)
Bearing is a mechanical component that supports loads and transmits rotation. As the application of high-value-added products such as semiconductors, aviation, and robots have recently become diverse and more precise, an accurate bearing performance prediction and evaluation technology is required. Bearing performance evaluation can be divided into evaluations based on bearing theory and on numerical analysis. An evaluation based on numerical analysis is a technique that has been highlighted because the problems that remained unsolved owing to time problems can be solved through recent developments in computers. However, current studies have the disadvantage of not considering the essential changes over time and bearing rotation. In this study, bearing performance evaluation based on rigid body dynamic analysis considering rotation and load over time is performed. Rigid body dynamic analysis is performed for deep groove ball bearing to calculate the load applied by the ball. The reliability of the analysis is verified by comparing it with the results calculated using bearing theory. In addition, rigid body dynamic analysis is performed for automotive wheel bearings to calculate the contact angle and load applied by the ball for cases where axial load and radial load are applied, respectively. The effect of rotation and load over time is evaluated from these results.